2019
DOI: 10.3390/microorganisms7080248
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Sequence Analysis of the Multidrug-Resistance Region of Avian Salmonella enterica serovar Indiana Strain MHYL

Abstract: A series of human and animal diseases that are caused by Salmonella infections pose a serious threat to human health and huge economic losses to the livestock industry. We found antibiotic resistance (AR) genes in the genome of 133 strains of S. Indiana from a poultry production site in Shandong Province, China. Salmonella enterica subsp. enterica serovar Indiana strain MHYL had multidrug-resistance (MDR) genes on its genome. Southern blot analysis was used to locate genes on the genomic DNA. High-throughput s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…By correlating the core genome to the genotypes of antibiotic resistance genes, we observed a high diversity of the antibiotic resistance genes in the predominant cluster of S. Kentucky isolates (Figure 2 and Table S6), indicating that the multidrug resistance of S. Kentucky was less related to the core genome. Previous studies showed that S. Kentucky were multidrug-resistance serotypes (38)(39)(40)(41), while S. Kentucky isolates in this study contained antibiotic resistance gene from more than five different antibiotic groups. S. Enteritidis isolates in this study showed a close relationship of the core genome clusters to the genotypes of its antibiotic resistance genes (Figure 3 and Table S7).…”
Section: Discussionmentioning
confidence: 57%
“…By correlating the core genome to the genotypes of antibiotic resistance genes, we observed a high diversity of the antibiotic resistance genes in the predominant cluster of S. Kentucky isolates (Figure 2 and Table S6), indicating that the multidrug resistance of S. Kentucky was less related to the core genome. Previous studies showed that S. Kentucky were multidrug-resistance serotypes (38)(39)(40)(41), while S. Kentucky isolates in this study contained antibiotic resistance gene from more than five different antibiotic groups. S. Enteritidis isolates in this study showed a close relationship of the core genome clusters to the genotypes of its antibiotic resistance genes (Figure 3 and Table S7).…”
Section: Discussionmentioning
confidence: 57%
“…It's regrettable of that overuse of antibiotics has increased the severity of salmonella [29]. The main reasons of drug resistance was that antibiotic resistance (AR) and multidrug-resistance (MDR) genes were in the genome of almost all Salmonella strains [30].…”
Section: Discussionmentioning
confidence: 99%
“…The following supporting information can be downloaded at: . References [ 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 ] are cited in the supplementary materials.…”
mentioning
confidence: 99%